Analgesia for major laparoscopic abdominal surgery: a randomised feasibility trial using intrathecal morphine. (17th January 2022) - Pirie, K.; Doane, M. A.; Riedel, B.; Myles, P. S.
Summary: Effective pain control enhances patient recovery after surgery. Laparoscopic techniques for major abdominal surgery are increasingly utilised to reduce surgical trauma. Intrathecal morphine is an attractive analgesic option that is gaining popularity. However, limited evidence guides its use in the setting of laparoscopic surgery. In addition, enhanced recovery after surgery pathways advocate opioid‐sparing techniques. We conducted a feasibility trial to compare intrathecal morphine with non‐neuraxial analgesia in laparoscopic or laparoscopic‐assisted major abdominal surgery to inform the design of a future large clinical trial. This multicentre, double‐blind, randomised controlled trial was conducted at two tertiary hospitals in Australia. Fifty‐one patients were randomly allocated to receive either intrathecal morphine (intervention group) or a sham subcutaneous injection of normal saline in the lumbar area (control group) immediately before the induction of general anaesthesia. Co‐primary outcomes were patient recruitment and successful adherence to treatment allocation as per the study protocol. The primary endpoints of feasibility and protocol adherence were met with a 46% recruitment rate (51 of 110 eligible patients) and 96% protocol adherence. There was only one patient with failed access to the intrathecal space. For secondary endpoints, fewer patients in the intrathecal morphine group required opioids in the post‐anaesthesia care unit, their postoperative pain scores at rest were lower across the four time‐points measured (p = 0.007), but not dynamic pain scores (p = 0.061), and pruritus was more common following intrathecal morphine (p = 0.007). Total oral morphine equivalents until postoperative day 3 were less in the intrathecal morphine group (median (95%CI) difference 82 (−13 to 168) mg), but this reduction was not statistically significant (p = 0.10). These findings support conducting a definitive clinical trial.